2013
DOI: 10.9787/pbb.2013.1.2.103
|View full text |Cite
|
Sign up to set email alerts
|

SSR Analysis of Genetic Diversity and Cold Tolerance in Temperate Rice Germplasm

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT A total of 23 elite rice cultivars from eight countries were evaluated for cold tolerance using two screening methods at Chuncheon Substation, National Institute of Crop Science (NICS), Republic of Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Evidently, the group B including the most superior rice accessions under low temperature conditions. these results are in agreement with the previous results which reported that Japonica type accessions are more cold tolerance than Indica type (Renata et al, 2010;Sanghera et al, 2011 andSuh et al, 2013). Due to the useful breeding programs are depending on modern and adapted knowledge of genetic diversity among varieties to utilize the available genetic resources to create new genotypes, morphological markers reflect not only the genetic contribution of the genotypes but also the interaction of the genotype with environment in which it is revealed (Thenmozhi and Rajasekaran, 2013).…”
Section: Cluster Based On Morphological Dendrogramsupporting
confidence: 94%
“…Evidently, the group B including the most superior rice accessions under low temperature conditions. these results are in agreement with the previous results which reported that Japonica type accessions are more cold tolerance than Indica type (Renata et al, 2010;Sanghera et al, 2011 andSuh et al, 2013). Due to the useful breeding programs are depending on modern and adapted knowledge of genetic diversity among varieties to utilize the available genetic resources to create new genotypes, morphological markers reflect not only the genetic contribution of the genotypes but also the interaction of the genotype with environment in which it is revealed (Thenmozhi and Rajasekaran, 2013).…”
Section: Cluster Based On Morphological Dendrogramsupporting
confidence: 94%
“…Minimum temperatures during the rainy season ranged from 18˝C to 25˝C while maximum temperatures ranged from 30˝C to 40˝C. (Avangard and Mustaqillik) and Korea (Jinbu) showed high cold tolerance under cold-water and greenhouse conditions showing 71% to 79% spikelet fertility [15,16]. Based on the hypothesis that the sowing date does not have any effect on the varieties, the objectives of this research were to identify cold tolerant rice genotypes that are adapted to the Sahel zone of West Africa and the agro-morphological traits associated with this adaptation.…”
Section: Air and Water Temperature In The Experiments Fieldmentioning
confidence: 99%
“…According to Dingkuhn and Miézan [14], temperatures below 18˝C can induce up to 50% sterility and this can reach up 100% at 10˝C in very sensitive varieties. In a study of reproductive stage cold tolerance conducted on 23 elite rice cultivars from eight countries, only accessions from Uzbekistan (Avangard and Mustaqillik) and Korea (Jinbu) showed high cold tolerance under cold-water and greenhouse conditions showing 71% to 79% spikelet fertility [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Five SSR markers were associated with spikelet fertility under a cool environment greenhouse on chromosomes 8, 9, 10, and 12. They conclude that SSR marker associated to cold tolerance may also be useful as selection markers in indica/ japonica cross combination to improve cold tolerance (Suh et al, 2013). Cconstructed a linkage map with 135 restriction fragment length polymorphism (RFLP) markers and 34 random amplified polymorphic DNA (RAPD) markers using 212 doubled-haploid lines (DHLs) to identify the chromosomal region controlling cool temperature tolerance (CT) at booting stage of rice.…”
Section: Molecular Basis Of Cold Tolerancementioning
confidence: 99%